COVID-19 and mental health in Australia - a scoping review - Yixuan Zhao; Liana S. Leach; Erin Walsh; Philip J. Batterham; Alison L. Calear; Christine Phillips; Anna Olsen; Tinh Doan; Christine LaBond; Cathy Banwell (BMC, 2022)
Abstract Background The COVID-19 outbreak has spread to almost every country around the world and caused more than 3 million deaths. The pandemic has triggered enormous disruption in people's daily lives with profound impacts globally. This has also been the case in Australia, despite the country's comparative low mortality and physical morbidity due to the virus. This scoping review aims to provide a broad summary of the research activity focused on mental health during the first 10 months of the pandemic in Australia. Results A search of the Australian literature was conducted between August-November 2020 to capture published scientific papers, online reports and pre-prints, as well as gaps in research activities. The search identified 228 unique records in total. Twelve general population and 30 subpopulation group studies were included in the review. Conclusions Few studies were able to confidently report changes in mental health driven by the COVID-19 context (at the population or sub-group level) due to a lack of pre-COVID comparative data and non-representative sampling. Never-the-less, in aggregate, the findings show an increase in poor mental health over the early period of 2020. Results suggest that young people, those with pre-existing mental health conditions, and the financially disadvantaged, experienced greater declines in mental health. The need for rapid research appears to have left some groups under-researched (e.g. Culturally and Linguistically Diverse populations and Indigenous peoples were not studied), and some research methods under-employed (e.g. there was a lack of qualitative and mixed-methods studies). There is a need for further reviews as the follow-up results of longitudinal studies emerge and understandings of the impact of the pandemic are refined.